The Silent Epidemic: Unmasking Community Risk Factors For Non-Communicable Diseases - John Leones Damo; Adriane Gabrille Perez (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Non-communicable diseases (NCDs) such as cardiovascular illnesses, diabetes, cancer, and chronic respiratory conditions have emerged as a silent epidemic, affecting millions globally and increasingly impacting Filipino communities. This study, titled